STRATEGI PENGEMBANGAN INDUSTRI KRIYA LOGAM DI DESA TUMANG CEPOGO BOYOLALI - Aan Sudarwanto; Kuntadi Wasi Darmojo (Corak : Jurnal Seni Kriya, 2018)
This article is the result of community service, taking the theme of the Development of Metal Craft Industry. The aim is to increase the competitiveness of the metal craft industry in the village of Tumang Cepogo Boyolali. With a focus on handling product quality and production speed so that they can compete as export products. The method or approach used in the development of the metal craft industry includes training education with lecture, interactive, guidance and mentoring techniques. Then the design and application supervision was carried out as well as the provision of appropriate technology equipment stimulation to solve production problems. The main problem of SMEs especially metal craft in Tumang village is the use of simple tools, which is one of the reasons why handicraft products cannot meet market demand in a short time. So we need a strategy on how to solve these problems. Besides that, there are many other problems that need handling as a form of development strategy. Among them are handling raw material problems, design, production tools, promotion strategies, marketing and management of human resources. The focus of this empowerment activity is more directed at aspects of improving the quality of metal handicraft production which includes strengthening production systems, strengthening human resources, utilizing appropriate technology use, design, design and product branding which ultimately lead to the export of metal craft products. Keywords: Empowerment, metal crafts, quality  Artikel yang merupakan hasil pengabdian pada masyarakat ini, mengambil tema Pengembangan Industri Kriya Logam. Adapun tujuannya untuk meningkatkan daya saing industri kriya logam yang berada di desa Tumang Cepogo Boyolali. Dengan menitikberatkan pada penanganan kualitas produk dan kecepatan produksi sehingga mampu bersaing sebagai produk ekspor.  Metode atau pendekatan yang digunakan di dalam pengembangan industri kriya logam ini  antara lain menggunakan pendidikan pelatihan dengan teknik  ceramah,  interaktif, bimbingan dan  pendampingan. Kemudian dilakukan supervisi  desain dan aplikasinya serta pemberian stimulasi  peralatan teknologi tepat guna untuk memecahkan persoalan produksi. Problem utama UKM khususnya kriya logam di desa Tumang adalah penggunaan alat yang sederhana, merupakan salah satu sebab mengapa produk kriya tidak bisa memenuhi permintaan pasar dalam waktu yang singkat. Sehingga diperlukan strategi bagaimana memecahkan permasalahan tersebut. Disamping itu banyak permasalahan-permasalahan lain yang diperlukan penanganan sebagai bentuk strategi pengembangan. Diantaranya penanganan permasalahan bahan baku, desain, alat produksi, strategi promosi, pemasaran dan pengelolaan sumber daya  manusia.Fokus dari kegiatan pemberdayaan ini lebih diarahkan pada pada aspek peningkatan kualitas produksi Kerajinan logam  yang meliputi penguatan sistem produksi, penguatan sumber daya manusia, pemanfaatan teknologi tepat guna, perancangan desain, dan branding produk yang akhirnya bermuara pada eksport hasil produk kerajinan logam. Kata kunci : Pemberdayaan, kriya logam, kualitas